ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KOMUNIKASI WORD OF MOUTH TERHADAP MINAT GUNA JASA ULANG (Studi Kasus pada PT. NASMOCO di Semarang) - Nuryulia P, Aflit (Master of Management Diponegoro University, 2009)
This research analyses factors influencing word communications of moth to re-service usage enthusiasm. This research object is PT. Nasmoco in Semarang. Research problems refers to business phenomenon PT. Nasmoco in Semarang. For the reason this research problems is as follows : what increasing re-service usage enthusiasm passed word communications of mouth. a model has been built and five research hypothesises has been formulated.Method purposif has been selected to obtain data required at this study. This research utilizes 145 respondents and overall of respondent is customers PT. Nasmoco in Semarang. Data analysis utilizes Structural Equation Model with computer program Amos 16. This research model has fulfilled criterion Goodness of Fit that is chi square =( 253,724); probability = (0,054); GFI = (0,871); AGFI = (0,838); CFI = (0,983); TLI = (0,980); RMSEA = (0,033); CMIN/DF =(1,159).Result of this research shows between it that quality of service of influential positive to communications wom. Customer satisfaction of influential positive to communications wom. Commitment influential positive to commitment wom. Strength of the relation of influential positive to communications wom. Communications wom influential postif to re-service usage enthusiasm.